Analisis Kelayakan Sistem Tumpangsari Jagung (Zea mays L.) dan Kacang Tanah (Arachis hypogea L.) di Kecamatan Lawa Kabupaten Muna Barat - Arisman, Arisman; Saediman, Saediman; Abdullah, Weka Gusmiarty (Department of Agribusiness, Halu Oleo University, 2020)
Feasibility of the Intercropping Systems of Maize (Zea mays L.) and Peanuts (Arachis hypogea L.) in Wamelai Village, Lawa Subdistrict, West Muna District